Parental school satisfaction in the context of segregation of basic education in urban Finland - Jenni Tikkanen (Co-Action Publishing, 2022)
This article examines the implications of the school choice policy, which has contributed to the segregation of basic education in urban Finland, by analysing the connection between the socio-economic status (SES) of schools’ student populations and parents’ satisfaction with their children’s schools. The 318 participants were parents of lower secondary school students attending socio-economically affluent, average, and disadvantaged schools in three Finnish cities. Multiple indicators multiple causes modelling, with school SES and parental education as covariates, was used to test the hypothesis that a school’s higher SES is connected to higher levels of parental school satisfaction with different aspects of the school’s functioning. The hypothesis was partially verified as the results showed that a higher SES of a school implied more parental satisfaction with home–school cooperation and school culture. The findings suggest that the social segregation of basic education in urban Finland has implications beyond the differentiation of students’ academic achievements and provide empirical evidence on the workings of one of the segregation mechanisms.